2017
DOI: 10.1111/ijn.12614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a family‐support programme for pregnant women with foetal abnormalities requiring pregnancy termination: A randomized controlled trial in China

Abstract: Aim: We examined the effects of a family-support programme for pregnant women with foetal abnormalities in terms of family support, depression, and post-traumatic stress symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…In the positive coping stage, women then made full use of support from relatives and started to plan for their future. Women highlighted that emotional and social support was of great significance to their psychological conditions, which was similar to previous research findings (Sun et al, 2018). Nurses should provide guidance on emotional, informational and behavioural support to family members because it can enhance the family's understanding of induced abortion decisions and increase the availability of interpersonal resources for women (Sun et al, 2018;Winograd, 2017).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the positive coping stage, women then made full use of support from relatives and started to plan for their future. Women highlighted that emotional and social support was of great significance to their psychological conditions, which was similar to previous research findings (Sun et al, 2018). Nurses should provide guidance on emotional, informational and behavioural support to family members because it can enhance the family's understanding of induced abortion decisions and increase the availability of interpersonal resources for women (Sun et al, 2018;Winograd, 2017).…”
Section: Discussionsupporting
confidence: 80%
“…Women highlighted that emotional and social support was of great significance to their psychological conditions, which was similar to previous research findings (Sun et al, 2018). Nurses should provide guidance on emotional, informational and behavioural support to family members because it can enhance the family's understanding of induced abortion decisions and increase the availability of interpersonal resources for women (Sun et al, 2018;Winograd, 2017). In addition, building a platform for communication among women with similar experiences and carrying out group psychological consultation could be beneficial (Zhang, Yu, Sun, Jia, & Yang, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…The majority of couples (72%) reported the need for contact with other people who had experienced a similar problem [39]. In a study from China, a group of women and their families, who were included in the intervention group and received psychological assistance during and after TOP, proved to have the lowest rate of subsequent psychological complications, such as post-traumatic stress and depression [40]. In the Polish reality, due to high social stigmatization, women tend to avoid support groups and contact with a psychologist, as they would then have to admit to having undergone termination.…”
Section: Discussionmentioning
confidence: 99%
“…In a well-functioning family, family members can detect the physical and psychological changes of women during pregnancy, and provide timely and effective spiritual and material help when pregnant women cope with stressor and crisis, so as to enhance their sense of family belonging, identity. 35 However, family dysfunction reflects that pregnant women can't acquire enough attention, love, identity and assistance from families, even family may be the source of mental pressure, so that depressive symptoms starts or aggravates. In this study, no significant association was found between moderate family dysfunction and depressive symptoms among women in their third trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%